Effect of surface hydrophobicity of therapeutic protein loaded in polyelectrolyte nanoparticles on transepithelial permeability - Miklavžin Ana; Cegnar Mateja; Kerč Janez; Kristl Julijana (Acta Pharmaceutica)
Oral delivery of protein drugs is greatly limited by low hydrophobicity, an important determinant for intestinal epithelial permeation and bioavailability. Herein, surface properties of recombinant erythropoietin were investigated using the fluorescent dye bis-ANS to monitor relative hydrophobicity for correlation with permeabilities with Caco-2 cells. At various pHs, bis-ANS fluorescence intensity indicated different surface hydrophobicities of erythropoietin molecules. Erythropoietin incorporated in chitosan or chitosan-trimethylchitosan (CS-TMC) nanoparticles prepared by polyelectrolyte complexation and ionotropic gelation with tripolyphosphate also showed different surface hydrophobicities. Chitosan nanoparticles with erythropoietin provided the most hydrophobic surface, followed by free erythropoietin (in water) and that loaded into CS-TMC nanoparticles. Chitosan nanoparticles were more effective than CS-TMC nanoparticles for permeation of erythropoietin across Caco-2 cell monolayers; the lowest permeability was shown by erythropoietin itself. Thus, hydrophilic protein molecules complexed with polyelectrolytes can provide more hydrophobic surfaces that enhance transepithelial permeability. This bis-ANS method also provides valuable information for the design of polyelectrolyte nanoparticules for oral delivery of protein drugs.